Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Inégales dans la tourmente - Couturier, Eve-Lyne; Posca, Julia (Institut de recherche sur les inégalités sociales (IRIS), 2021)
↘ Que ce soit au chapitre de l’emploi ou de la maladie, les femmes québécoises ont été davantage affectées par la pandémie que les hommes. ↘ La position désavantagée des femmes sur le marché du travail les rend, dans les années qui suivent un ralentissement économique, plus vulnérables. ↘ La crise environnementale risque d’affecter plus lourdement les femmes, dont les femmes autochtones au Canada, étant donné la part des tâches liées au soin des personnes qui leur incombent. ↘ Les plans de relance économique ou de transition écologique des gouvernements du Québec et du Canada ne tiennent pas compte de la situation des femmes dans l’économie et risquent ainsi de contribuer à reproduire les inégalités de genre au pays.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; capitalisme; inégalités; pandémie; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques

Gender differences in emotional response to the COVID‐19 outbreak in Spain - García‐Fernández, Lorena; Romero‐Ferreiro, Verónica; Padilla, Sergio; David López‐Roldán, Pedro; Monzó‐García, María; Rodriguez‐Jimenez, Roberto (Brain and Behavior, 2021)
We aim to explore the differential presence of symptoms of anxiety, depression, and acute stress between men and women during the COVID-19 outbreak, and to study the relationship between these symptoms and two environmental variables, coexistence, and violence.We conducted a cross-sectional study starting on March 29 to April 5, 2020, based on a national online survey using snowball sampling techniques. Symptoms of anxiety (Hamilton Anxiety Scale), depression (Beck Depression Inventory), and acute stress (Acute Stress Disorder Inventory) were assessed. Differences in the presence of symptoms and the relationship of coexistence and domestic violence were evaluated from a gender perspective.Men showed significant lower mean (SD) in anxiety, depression, and acute stress levels than women [HARS, 14.1 (9.8) versus. 18.4 (10.2), F = 56.2, p < .001; BDI 3.4 (3.9) versus 4.5 (4.3), F = 16.6, p < .001, and ASDI 3.6 (2.9) versus 4.7 (3.1), F = 39.0, p < .001, respectively), as well as a weaker depressive syndrome (28.1% males versus 39.9% females, χ2 = 25.5, p < .001). In addition, an interaction Gender × Coexistence was found in anxiety (F = 56.2, p < .001) and acute stress (F = 3.52, p = .06) and, according to depressive symptoms, an interaction Gender × Violence was found marginally significant (F = 3.3, p = .07).Findings indicate that women present greater severity in symptoms of anxiety, depression, and acute stress. Moreover, loneliness and violence specifically worsen the emotional state in women. These results can undoubtedly guide better healthcare planning adopting a gender perspective.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; covid-19; espagne; europe; genre; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; violences; violences conjugales; étude quantitative

Patriarcavirus, feminist dystopias and COVID-19: Reflections on the phenomenon of gender pandemics - Machado-Jiménez, Almudena (Feminismo/s, 2021)
This essay examines contemporary feminist dystopias to study the phenomenon of gender pandemics. Gender pandemic narrative allegorises possible aftermaths of patriarcavirus, unleashing many natural disasters that force global biopolitics to hinder gender equality. The main objective of this essay is to explain how gender pandemics are appropriated in patriarchal utopian discourses as a pretext to control female empowerment, diagnosing women as diseased organisms that risk the state’s well-being. Moreover, the novels explore the interdependence between biology and sociality, portraying the acute vulnerability of female bodies during and after the pandemic conflicts, inasmuch as patriarchal power arranges a hierarchical value system of living that reinforces gender discrimination. Particularly, the COVID-19 emergency is analysed as a gender pandemic: the exacerbated machismo and the growing distress in the female population prove that women are afflicted with a suffocating patriarcavirus, which has critically gagged them in the first year of the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; arts; corps; covid-19; discipline; droits des femmes*; genre; patriarcat; précarité; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques; violences; études littéraires

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Au-delà de la COVID-19: un plan féministe pour la durabilité et la justice sociale - Staab, Silke; Tabbush, Constanza; Turquet, Laura; Williams, Loui (ONU Femmes, 2021)
Alors que le monde apprend à vivre avec le COVID-19, à « reconstruire en mieux » et est mobilisé pour sortir de la crise actuelle, le nouveau « Plan féministe » d’ONU Femmes fournit une feuille de route visionnaire mais concrète visant à placer l’égalité des sexes, la justice sociale et la durabilité au centre de la relance et de la transformation. Le COVID-19 a révélé et aggravé les inégalités et rappelle à quel point les économies et les démocraties du monde sont insoutenables et fragiles. La crise met également en garde contre les changements climatiques et la dégradation de l'environnement imminents. Ceci a créé à la fois le besoin et l’opportunité de repenser les politiques économiques et sociales et de réévaluer ce qui doit être priorisé. Le « Plan féministe » cartographie les politiques ambitieuses et transformatrices relatives aux moyens de subsistance, aux soins et à l'environnement qui sont nécessaires pour construire un avenir plus équitable et durable. Pour y parvenir, il appelle à des approches politiques spécifiques au contexte, à des stratégies politiques adaptées et à un financement. Le plan identifie les leviers clés qui peuvent créer un changement ainsi que les actrices et acteurs aux niveaux mondial, national et local qui doivent prendre des mesures pour avancer vers cette vision.
Keywords: 2000 à aujourd'hui; OFDIG; approches et analyses; covid-19; droits des femmes*; femmes*; inégalités; justice sociale; politique; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences